Reimagining the national security state : liberalism on the brink / edited by Karen J. Greenberg. - Greenberg, Karen J. (Cambridge University Press, 2020)
Reimagining the National Security State provides the first comprehensive picture of the toll that US government policies took on civil liberties, human rights, and the rule of law in the name of the war on terror. Looking through the lenses of theory, history, law, and policy, the essays in this volume illuminate the ways in which liberal democracy suffered at the hands of policymakers in the name of national security. The contributors, who are leading experts and practitioners in fields ranging from political theory to evolutionary biology, discuss the vast expansion of executive powers, the excessive reliance secrecy, and the exploration of questionable legal territory in matters of detention, criminal justice, targeted killings, and warfare. This book gives the reader an eye-opening window onto the historical precedents and lasting impact the security state has had on civil liberties, human rights and, the rule of law in the name of the war on terror.